Accuracy improvement of the modified EDM model for non-premixed turbulent combustion in gas turbine. (September 2015) - Li, Qiong; Yang, Hui; Wang, Yanpeng; Wang, Peiyong
Abstract: Eight bluff body and swirl turbulent diffusion flames resembling the flow field and combustion inside gas turbine combustors are simulated and the simulation results are compared with experimental data. It is revealed that the original modified EDM model could not predict the temperature profile accurately. A more accurate model is developed and validated for gas turbine combustion application. However, this model under predicts the flame temperature for the regular round jet flames indicating that no universal form of the modified EDM model could be achieved for the combustion simulation of both gas furnaces and gas turbines.